Comparative Analysis of Stock Returns, Abnormal Return and Tranding Volume Activity for Christmas Event in 2022 LQ 45 Company on The IndonesianStock Change. - Ananda Ifan Maulana; Wulan Suryandani (Jurnal Ilmu Manajemen Profitability, 2024)
This research focuses on analyzing the impact of Christmas events on LQ 45 companies listed on the Indonesia Stock Exchange in 2022. The research background underlines the importance of capital markets in the economy, where investors seek to understand changes in stock returns, abnormal returns, and activity. trading volume in connection with special events such as Christmas. The aim of the research is to determine significant differences in stock performance, abnormal returns and trading activity before and after the Christmas event at LQ 45 companies during the 2022 period. The method used is event study analysis with a purposive sampling technique for 45 companies. The research results show that there is no significant difference in trading volume activity before and after Christmas, while stock returns and abnormal returns show significant differences during the 5 day period before and after Christmas. The conclusion of this research is that the Christmas event has a significant impact on stock returns and abnormal returns of LQ 45 companies on the Indonesia Stock Exchange in 2022, but does not make a significant difference in trading volume activity. The implication is that investors and decision makers may consider events such as Christmas in making their investment decisions, considering the impact it can have on stock performance.